The Influence of English Youtube Videos on The Disoriented Language of The Mother Tongue Among Young Children on Their Language Development Process - Paulina Novarita; Wahyu satya Gumelar; Nur Ainun (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the influence of prolonged exposure to English-language YouTube videos on the disruption of mother tongue development among young children in Indonesia. Set within the growing relevance of digital media in early language acquisition, this qualitative research adopts a case study design involving seven children aged 3 to 7 years who are currently receiving speech therapy in Bandung. Data were obtained through in-depth interviews with parents and non-participant observations of the children's communicative behaviors. Findings indicate a recurring pattern of language interference, including frequent code-mixing between English and Bahasa Indonesia, limited mastery of native vocabulary, and dependence on non-verbal cues such as gestures or incomplete phrases. For instance, several children were observed substituting basic Indonesian words with English counterparts (e.g., “open” instead of buka), or forming syntactically incorrect sentences influenced by English structure. These disruptions are closely associated with the predominance of English-language input during daily screen time and a marked reduction in native language interaction—particularly during the COVID-19 lockdown period. The study underscores an imbalance in bilingual exposure, wherein English increasingly replaces Bahasa Indonesia in daily expression, potentially contributing to expressive language delays and syntactic confusion. To address these challenges, the research recommends increased parental mediation, purposeful mother tongue engagement at home, and implementation of media literacy programs tailored to early childhood contexts. While the study provides valuable insights into media-induced linguistic shifts in multilingual settings, it is limited by its small sample size and specific geographic focus. Future research should explore longitudinal outcomes and include diverse socio-cultural contexts to enhance generalizability.